Workforce Development in Emerging Economies : Comparative Perspectives on Institutions, Praxis, and Policies - Tan, Jee-Peng (Washington, DC: World Bank, 2016)
Investing in skills has risen to the top of the policy agenda today in rich and poor countries alike. The World Bank supports its partner countries on this agenda in multiple ways: development finance, research and analysis, global knowledge exchange, and technical assistance. This report was originally conceived as a contribution to this catalog of the World Bank’s work, but its topic and findings are relevant to all policy makers and analysts interested in skills-building to drive economic growth and improve human well-being.